Dispersion-based, scalable fabrication of repellent superhydrophobic and liquid-infused coatings under ambient conditions - Walter, Teresa; Hein, Tamara; Weichselgartner, Matthias; Wommer, Kirsten; Aust, Martin; Vogel, Nicolas (Green Chemistry, 2022)
Superhydrophobic and liquid-infused porous coatings provide effective repellency against contaminations and ensure efficient performance of surfaces in a wide range of applications. Conventional fabrication processes of such coatings typically require fluorinated components, toxic solvents, and elevated temperatures, and therefore contribute to environmental pollution. Here, we present a dispersion-based, fluorine-free coating system that produces highly repellent surface coatings at ambient conditions. Our system is based on aqueous dispersions of a polymeric binder and hydrophobic fumed silica particles, which upon drying self-organize into a micro- and nanostructured thin film with superhydrophobic properties, characterized by a water contact angle above 150 degrees and a contact angle hysteresis below 10 degrees. An additional dispersion-based coating step allows infusing these structures with silicone oil, thus producing a lubricant-infused repellent coating mimicking the pitcher plant. Water droplets on such coatings exhibit efficient repellency properties, characterized by low sliding angles (<5 degrees) and contact angle hysteresis of water droplets (<10 degrees). Our method provides a versatile, dispersion-based toolbox to create functional, repellent coatings in a simple, scalable and environmentally benign process.